Microencapsulation of Chromolaena odorata Leaf Extract with Cellulose Esters for the Application as an Eco-Friendly Antibacterial Agent - Ketwaraporn, Jiraporn; Pinthong, Somyod; Kerdphu, Rungnapha; Daebau, Surahani; Kraivuttinun, Parinya; Jansanthea, Pongthep (Indonesian Journal of Chemistry, 2024)
The aim of this work is to develop an eco-friendly antibacterial agent in the form of microcapsules containing extract from Chromolaena odorata leaves using the solvent evaporation method. The wall materials for encapsulating were tested with various cellulose esters including cellulose acetate (CA), cellulose acetate butyrate (CAB), and cellulose acetate propionate (CAP). The evaluation of microcapsules containing C. odorata leaf extract was focused on their encapsulation efficiency, size, shape, thermal stability, and antimicrobial activities. The results showed that CAB was a suitable wall material for the encapsulation of C. odorata leaf extract. The CAB microcapsules exhibited the highest encapsulation efficiency, which was 65.82 ± 3.07. The size of CAB microcapsules was the smallest, at 1013.3 ± 66.5 nm. According to the thermogravimetric analysis, the prepared microcapsules were able to protect the extract of C. odorata leaves from the environment. Moreover, the CAB microcapsules containing C. odorata leaf extract showed the best antibacterial activities against Escherichia coli ATCC 25922 and Stapphylococcus aureus ATCC 25923. The minimum bactericidal concentration of the microcapsules was 25.6 mg/mL in both bacteria. This study proved the potential application of C. odorata leaf extract as a biomaterial in diverse industries in the future.